ALUR PELACAKAN PEMBALAKAN LIAR (ILLEGAL LOGGING) MELALUI PENDEKATAN PENCUCIAN UANG - Lucky Nurhadiyanto (SISI LAIN REALITA, 2016)
Illegal logging is a part of crime against environment, which has a massive impact on the economy, social, cultural, and ecological. Ironically, majority of the illegal logging’s perpetrators are dominated by “the field criminal”. On the other side, intellectual actors who can control the activities never touch by the law. The money laundering concept can give a new approach to detect the leader actor. The author use follow the money viewpoint, which includes placement, layering, and integration. Qualitative data collection methods is used with in-depth interviews, systematic observation of the behavior, and document analysis. The result is a new paradigm in investigating illegal logging no longer focused on the field actors, but potentially tracking the intellectual actors behind illegal logging.